An Anatomical Study of Maxillary-Zygomatic Complex Using Three-Dimensional Computerized Tomography-Based Zygomatic Implantation. (11th December 2017) - Xu, Xiangliang; Zhao, Shijie; Liu, Hui; Sun, Zhipeng; Wang, Jianwei; Zhang, Weiguang
Abstract : Objective. To obtain anatomical data of maxillary-zygomatic complex based on simulating the zygomatic implantation using cadaver heads and three-dimensional computerized tomography (3D-CT). Methods. Simulating zygomatic implantation was performed using seven cadaver heads and 3D-CT images from forty-eight adults. After measuring the maxillary-zygomatic complex, we analyzed the position between the implantation path and the maxillary sinus cavity as well as the distance between the implantation path and the zygomatic nerve. Results. The distance from the starting point to the endpoint of the implant was 56.85 ± 5.35 mm in cadaver heads and 58.15 ± 7.37 mm in 3D-CT images. For the most common implantation path (80.20%), the implant went through the maxillary sinus cavity completely. The projecting points of the implant axis (IA) on the surface of zygoma were mainly located in the region of frontal process of zygomatic bone close to the lateral orbital wall. The distances between IA and zygomatic nerve in 53 sides were shorter than 2 mm. Conclusion. The simulating zygomatic implantation on cadaver skulls and 3D-CT imaging provided useful anatomical data of the maxillary-zygomatic complex. It is necessary to take care to avoid the zygomatic nerve injury during implantation, because it frequently appears on the route of implantation.